Response to Indacaterol/Glycopyrronium (IND/GLY) by Sex in Patients with COPD: A Pooled Analysis from the IGNITE Program. (4th July 2017) - Tsiligianni, Ioanna; Mezzi, Karen; Fucile, Sebastian; Kostikas, Konstantinos; Shen, Steven; Banerji, Donald; Fogel, Robert
ABSTRACT: In this pooled analysis, we compared the effect of indacaterol/glycopyrronium (IND/GLY) by sex versus other commonly used chronic obstructive pulmonary disease (COPD) treatments and placebo. Male and female patients with moderate-to-very-severe COPD who had participated in six randomized controlled trials were included in the analysis. Baseline demographics and disease characteristics were analyzed by sex, and any differences noted. The effects of IND/GLY versus salmeterol/fluticasone (SFC), glycopyrronium, tiotropium and placebo, on lung function and the patient-reported outcomes (health status, dyspnea, rescue medication use and symptoms) were assessed by sex after 26 weeks treatment. The analysis population comprised 4719 men and 1389 women. Most baseline parameters differed significantly between men and women. Nonetheless, despite these differences in baseline characteristics, IND/GLY significantly improved lung function versus placebo ( p < 0.0001) and all active comparators ( p < 0.01) in men and women. Overall, IND/GLY showed better improvement in dyspnea and health status compared with all other treatments in both sex. Greater reduction of rescue medication use was observed with IND/GLY versus placebo and other treatments (all p < 0.01 expect IND/GLY versus SFC). Although some variability was observed, improvements in health status, dyspnea, rescue medication use and symptoms were generally larger in women than in men. Irrespective of sex, IND/GLY provided superior efficacy to monotherapy or SFC in both men and women. Small differences in efficacy response by sex were observed, which should be evaluated further in prospective clinical studies. Nevertheless, the benefits observed with IND/GLY confirm dual bronchodilator as the preferred therapy in patients with moderate-to-very-severe COPD regardless of sex.